PENGARUH ORGANISASI REMAJA MASJID AINUL YAQIN DALAM MENINGKATKAN KARAKTER ISLAMI BAGI MAHASISWA DI LINGKUNGAN UNIVERSITAS ISLAM MALANG - Mutoharoh Mutoharoh; Nur Hasan; Khoirul Asfiyak (VICRATINA, 2019)
This study aims to determine the influence of the organization of youth mosque activities in improving Islamic character for students. This research was conducted at the Islamic mosque organization Ainul Yaqin starting from April to June 2019. The research was aimed at students who took part in the activities of the youth mosque organization with a total population of 60 students and then th e entire sample was taken from the population. The data obtained from questionnaire data, prerequisite analysis techniques using two prerequisites with normality tests and linearity tests. While the hypothesis testing technique uses simple regression. The results of the study show that there is no relationship between the activities of the mosque's youth organizations in improving Islamic character for students. With the calculation of the significance value of 0.711> 0.5 and Tcount of 0.372 <T table 2.00172.